Respostas
respondido por:
5
x² - 6x + 4
a = 1; b = -6; c = 4
Delta:
Δ = b² - 4ac
Δ = (-6)² - 4 * 1 * 4
Δ = 36 - 16
Δ = 20
Vértice de x:
Xv = - b / 2a
Xv = - (-6) / 2 * 1
Xv = 6 / 2
Xv = 3
Vértice de y:
Yv = - Δ / 4a
Yv = - 20 / 4 * 1
Yv = - 20 / 4
Yv = -5
Espero ter ajudado. Valeu!
a = 1; b = -6; c = 4
Delta:
Δ = b² - 4ac
Δ = (-6)² - 4 * 1 * 4
Δ = 36 - 16
Δ = 20
Vértice de x:
Xv = - b / 2a
Xv = - (-6) / 2 * 1
Xv = 6 / 2
Xv = 3
Vértice de y:
Yv = - Δ / 4a
Yv = - 20 / 4 * 1
Yv = - 20 / 4
Yv = -5
Espero ter ajudado. Valeu!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás